Implementasi Program Listrik Pintar (Prabayar) di PT. Perusahaan Listrik Negara/PLN (Persero) Unit Layanan Pelanggan Pancur Batu - Elga Theofani Angela Br Tarigan; R. Sally Marisa Sihombing (UNIVED PRESS, Universitas Dehasen Bengkulu, 2023)
PT. PLN (Persero) is the only company that provides services to the public in the provision of services related to the sale of electric power in Indonesia. In the implementation of the smart electricity program (prepaid) there are several weaknesses in terms of the lack of public interest in using smart electricity (prepaid), problems with usage costs and network disruptions for online purchases. The purpose of this research is to find out how the Implementation of Smart Electricity Program (Prepaid) at PT. PLN (Persero) Customer Service Unit Pancur Batu. This research uses descriptive research method with a qualitative approach. Data collection techniques were carried out by means of interviews, observation, and documentation. The data that has been obtained is then analyzed qualitatively by reviewing all the data collected and supported by the results of interviews using the theory proposed by Van Meter and Van Horn related to policy standards and objectives, resources, characteristics of implementing agents, social and economic conditions, disposition of implementors, and communication between implementing agencies. Based on the results obtained from interviews, observations, and documentation, it is known that the Implementation of the Smart Electricity Program (Prepaid) at PT. PLN (Persero) Customer Service Unit Pancur Batu has not been running well because there are several obstacles such as lack of socialization and promotion resulting in a lack of public interest in using smart electricity (prepaid), lack of communication or coordination with partnerships so that the Smart Electricity Program Implementation process (Prepaid) has not been effective.